Immediate outcome of neonates with maternal hypertensive disorder of pregnancy at a neonatal intensive care unit - Hassan, Mahmuda; Begum, Marium; Haque, SM Zabrul; Jahan, Nasim; Yasmeen, BH Nazma; Mannan, Abdul; Choudhury, Kona; Rahman, Hamidur (Northern International Medical College Journal, 2015)
Aims : Hypertensive disorders in pregnancy remain a major cause of maternal and neonatal morbidity and mortality worldwide. This study prospectively examined the immediate neonatal outcome of women with maternal hypertensive disorder of pregnancy( HDP). Methods : Sixty mothers and their newborn were selected. Mothers with gestational hypertension, preeclampsia, preeclampsia superimposed on chronic hypertension and chronic hypertension were included. Results : Forty five (75%) mothers were mutipara and 15(25%) were primipara. Mean maternal age was 26.4 years. Mean gestational age was 34+4 weeks. 38 were male and 22 were female with Male: Female ratio was 1.72: 1. Thirty six (60%) were from in patient with regular antenatal check up, 60% mothers had gestational hypertension. Fifty four (90%) mothers needed lower uterine caesarian section. Forty four (73.33%) delivered preterm before 36 weeks of pregnancy. Low birth weight (<2.5kg) babies were 30(50%), very low birth weight (<1.5kg) were 16(26.66%). Intrauterine growth retardation (IUGR) were 18(30%) and Appropriate for gestational age( AGA) were 14(23.33%). Respiratory distress 30(50%) were the most common cause of admission, other associated problems were perinatal asphyxia (PNA) with seizure and meconium aspiration syndrome and to rule out sepsis in suspected cases. Nine (15%) needed ventilator care and 6(10%) needed nasal continuous positive airway pressure (NCPAP) for respiratory problem. 6(10%) babies were expired and 54(90%) survived. Average hospital stay were 18.32(±10.68) days with a highest hospital stay of 49 days and the lowest 4 days. Conclusion : Maternal hypertensive disorder of pregnancy is associated with neonatal morbidity. Northern International Medical College Journal Vol.6(2) 2015: 57-60